Unleashing the Presence of Eroticism in the Philippine Culture through a Multimodal Analysis of Viva Max Advertisements - Dizon, Jr., Rodolfo P.; Ravina, Elimar A. (Future Science / FSH-PH Publications, 2024)
Technological advancements have mainstreamed online advertisements in potentially meeting a wide array of viewers through the combination of texts and images. The integration leads to the emergence of the multimodal discourse analysis which constitutes broader semiotic resources in the construction of meaning. Working together, these resources contain elements that can represent a cultural identity. With that, this study explored how the presence of eroticism in the Philippine culture is reflected in the selected seven Viva Max online advertisements through a multimodal analysis of their linguistic elements and visual grammar. Using Halliday’s Systematic Functional Linguistics, the ideational, interpersonal, and textual metafunctions reveal that the participants, Filipino women, are highlighted as sex objects. They trade their chastity by alluring and initiating sexual intercourses in exchange of material possessions. Moreover, same sex relationships have been normalized in the Philippine society despite its deep catholic beliefs. Consistently, using Kress and Van Leeuwen (2006) Visual Grammar, representational and interactive analyses show participants having seductive poses, revealing outfits, and fierce facial expressions to show dominance over the viewers. These deconstruct the power women have in sexual intercourses. Overall, the eroticism in the Philippine culture reflects how women have remained men’s weaknesses in gratifying their sexual desires.